2022
DOI: 10.3892/etm.2022.11581
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑203a‑3p suppresses endothelial cell proliferation and invasion, and promotes apoptosis in hemangioma by inactivating the VEGF‑mediated PI3K/AKT pathway

Abstract: Our previous study demonstrated that was involved in the regulation of long non-coding RNA MEG8-mediated the progression of hemangioma, which is a benign tumor characterized by endothelial hyperplasia in the blood vessels and primarily occurring in infants and females. Therefore, the present study aimed to further investigate the effects of miR-203a-3p on endothelial cell proliferation, invasion and apoptosis, as well as its underlying mechanism in hemangioma. Human hemangioma endothelial cells (HemECs) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Our previous study reported that miR-203a-3p inhibits the PI3K/AKT pathway to facilitate hemangioma progression ( 24 ). Therefore, the effect of 740 Y-P, an activator of PI3K, was analyzed in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study reported that miR-203a-3p inhibits the PI3K/AKT pathway to facilitate hemangioma progression ( 24 ). Therefore, the effect of 740 Y-P, an activator of PI3K, was analyzed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Following transfection, HemECs were collected for detection of miR-203a-3p expression with RT-qPCR as previously described ( 24 ). In brief, total RNA was isolated using the RNeasy Mini kit (Qiagen GmbH).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of VEGFA alone promotes the invasion and proliferation of HemECs but reduces apoptosis. 37 Deletion of VEGF can abolish IL-6-induced HA progression. 38 VEGF induces VEGFdependent activation of VEGFR2 to facilitate HemEC growth.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we conducted functional rescue assays by silencing HIF‐1α and introducing pcDNA3.1 VEGF into HemECs simultaneously and elaborated that overexpression of VEGF decreased HemECs arrest at the G0/G1 phase, repressed the apoptosis, and facilitated the viability, proliferation, invasion, migration, and tubular formation of HemECs. Overexpression of VEGFA alone promotes the invasion and proliferation of HemECs but reduces apoptosis 37 . Deletion of VEGF can abolish IL‐6‐induced HA progression 38 .…”
Section: Discussionmentioning
confidence: 99%